The Psychopaths’ Moral Decision Making - Lieck, Katrin (ANIMA Indonesian Psychological Journal, 2013)
The present paper will investigate whether psychopaths are more prone to make utilitarian decisions in moral dilemmas. This ‘talent’ may be caused by a dysfunction in emotional brain circuits in psychopaths. Since utilitarian decisions are seen as the ‘right’ decision – in an economic point of view - one can make in moral dilemmas, it is interesting to see, whether psychopathic traits may also have its advantages. Studi pendahuluan ini meneliti apakah para psikopat cenderung membuat putusan bermanfaat dalam dilema moral. “Talenta” ini mungkin disebabkan disfungsi dalam sirkuit emosional di otak para psikopat. Karena putusan bermanfaat dilihat sebagai putusan yang “benar” – dari sudut pandang ekonomis – yang dapat diambil dalam dilemma moral, adalah menarik melihat, apakah sifat-sifat psikopat juga memiliki kelebihannya juga.